INTERPERSONAL INTELLIGENCE OF UPPER PRIMARY STUDENTS IN KOTTAYAM DISTRICT - SUSHMITHA S. KAMATH; THARA SEBASTIAN (The Journal of Research ANGRAU, 2024)
The research was conducted in the sub-districts of Kottayam and Pala, within the Kottayam educational district. A total of 550 fifth-grade students (343 girls and 207 boys) following both state and CBSE syllabus from different type of schools (government, aided and unaided) and areas (urban schools and rural schools) were obtained using stratified random sampling. A multiple intelligence checklist, developed by the researcher, was utilized as the tool for this study. The statements about interpersonal intelligence had a cronbach’s alpha value of 0.76. Using the testretest method, spearman-brown coefficient, and guttman split-half coefficient value ranged from 0.78 to 1. The tool was validated by subject matter experts. The data was evaluated through the application of multiple statistical techniques. The results showed that more than half of the students had strong interpersonal intelligence (57.3%), with significant differences in gender, area and type of school. There was no notable difference observed between interpersonal intelligence and family type